2006
DOI: 10.1542/peds.2005-1329
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Psychological Predictors of Body Fat Gain Among Children at High Risk for Adult Obesity

Abstract: Children's reports of binge eating and dieting were salient predictors of gains in fat mass during middle childhood among children at high risk for adult obesity. Interventions targeting disordered eating behaviors may be useful in preventing excessive fat gain in this high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
211
4
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(231 citation statements)
references
References 42 publications
13
211
4
3
Order By: Relevance
“…Data also suggest that LOC eating may predispose children to weight gain and obesity (Tanofsky-Kraff et al, 2006, 2009c. The mechanisms are not fully understood, but a preference for palatable foods during LOC episodes may place children at risk for excess energy intake long-term.…”
Section: Disordered Eating In Obese Children and Adolescentsmentioning
confidence: 99%
“…Data also suggest that LOC eating may predispose children to weight gain and obesity (Tanofsky-Kraff et al, 2006, 2009c. The mechanisms are not fully understood, but a preference for palatable foods during LOC episodes may place children at risk for excess energy intake long-term.…”
Section: Disordered Eating In Obese Children and Adolescentsmentioning
confidence: 99%
“…4,[6][7][8] A recent prospective, longitudinal study of children aged 6-12 demonstrated that children who engaged in binge eating gained an additional 15% more fat mass compared to children who did not binge eat. 9 Given the potentially chronic nature of the disorder, studies aimed at identifying, measuring, and treating BED in children are much needed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Fairburn et al 10 studying the longitudinal course of binge eating in the community over a 5-year period, found that, while binge eating was strikingly unstable over time, the prevalence of obesity in the sample had nearly doubled by the end of the study. Several studies of adolescents have reported associations between binge eating and upward weight trajectory, [11][12][13][14] although Stice et al 15 in a recent study of 11-to 15-year-old girls observed over a 4-year period, did not find binge eating to be associated with obesity onset.…”
Section: Obesogenic Binge Eating Disordermentioning
confidence: 96%